Research on Trend Analysis and Early Warning Technology of Smart Substation Telemetry Data Based on ARIMA-BP Combined Model - ZHOU Ke; WANG Xiaoming; LI Xiaobo; SONG Yi (Journal of Harbin University of Science and Technology)
In order to perform fault early warning on the secondary protection devices of smart substations based on monitoring data, a trend analysis and early warning method of smart substation telemetry data based on the ARIMA-BP combined model is proposed.Based on the analysis of the relay protection failure of the intelligent substation, the remote measurement data source for the early warning of the device status trend is selected, and the ARIMA-BP combined forecasting model is established based on the analysis of the characteristics of the data source.Based on the ARIMA-BP combined forecasting model and the historical telemetry data of the equipment, the equipment operation trend prediction is carried out.Taking the remote measurement data of the line protection device in a 220kV substation as an example, the prediction error rate of the ARIMA-BP combined model is 5% and 9% lower than that of the ARIMA model and the BP model alone. The superiority of ARIMA-BP combined model in telemetry trend prediction and early warning is verified.